2011
DOI: 10.1093/nar/gkr338
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach sheds new light on Escherichia coli acid resistance

Abstract: In order to develop an infection, diarrhogenic Escherichia coli has to pass through the stomach, where the pH can be as low as 1. Mechanisms that enable E. coli to survive in low pH are thus potentially relevant for pathogenicity. Four acid response systems involved in reducing the concentration of intracellular protons have been identified so far. However, it is still unclear to what extent the regulation of other important cellular functions may be required for survival in acid conditions. Here, we have comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 74 publications
8
93
0
Order By: Relevance
“…The genes ompR and ompC also have a role in acid tolerance of E. coli. Significant upregulation of ompC has been observed due to acid shock of E. coli [25], while the strong acid sensitivity of E. coli has been reported by deleting ompR [26]. In our experiment, we observed the downregulation of ompF (2.33-fold down), but the transcription of gene ompC (1.01-fold down) was found to be unchanged.…”
Section: Anion Effectssupporting
confidence: 46%
“…The genes ompR and ompC also have a role in acid tolerance of E. coli. Significant upregulation of ompC has been observed due to acid shock of E. coli [25], while the strong acid sensitivity of E. coli has been reported by deleting ompR [26]. In our experiment, we observed the downregulation of ompF (2.33-fold down), but the transcription of gene ompC (1.01-fold down) was found to be unchanged.…”
Section: Anion Effectssupporting
confidence: 46%
“…Although the OmpR regulons were found to differ in the two species, with only a few common targets, OmpR controls genes involved in pH homeostasis and acid stress response in both E. coli and Salmonella . In agreement with this, OmpR appears to play an important role in acid resistance (11). At least 4 small RNAs (sRNAs) are also known to be controlled by EnvZ-OmpR: MicC, MicF, OmrA and OmrB (1214) (see below).…”
Section: Introductionmentioning
confidence: 54%
“…Recently, it was also shown that an OmpR mutant is unable to survive even mild acid stress [71]. OmpR is thought to be regulated by IHF, Crp, and ppGpp.…”
Section: Resultsmentioning
confidence: 99%